ANALISA KESELARASAN PROGRAM KERJA KOMUNITAS PENCINTA SEDEKAH INHIL (KPSI) DENGAN INDIKATOR - INDIKATOR SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Raju Maulana (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2018)
The community of Inhil alms lover /Komunitas Pecinta Sedekah Inhil (KPSI) is non-profit organizations which was founded in 2012. It has ben confirmed by notary certification no 4 date 14th January 2013 by Erni Riyanti, SH., M. Kn. The source of fund of KPSI are compulsory and voluntary donations from the members and contributors. Some of the social activities are house construction for reading Al-Qur’an teachers and poor people, contributing sembako, fresh water in drought, education for scavenger children and others. SDGs are 17 goals, 169 targets and 241 indicators in social dimension coverage, economic and environment, law and governance. In order to support the SDGs administration, this study is required by KPSI to align between the workplan and indicators of SDGs. Based on desk review, it can be concluded that the KPSI participation was not only in social pillar, but it is also could provided the achievement acceleration of SDGs in environment pillar. Based on desk review, it can be concluded that KPSI workplan is conformed to 6 goals, 7 targets and 7 indicators which distributed in social pillar and environment.